PENERAPAN TEKNIK CETAK DAN FINISHING DALAM PENGEMBANGAN PRODUK KERAMIK DI PANNCRAFT WURYOREJO WONOGIRI - Nanang Yulianto; MY. Ning Yuliastuti; Slamet Supriyadi (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
The development of ceramic design is one of product development efforts that purpose to improve the quality and quantity of ceramic products manufactured by Pann Craft in Wuryorejo Wonogiri. The product quality intended related to product visualization, while the products quantity related to the effectivness and efficiency production process. The design development was obtained by applying the method of interviews and observations that are implemented with training and mentoring approach to participatory-explorative. It was obtained by applying the techniques of printing and innovative finishing techniques, expected to answer the demands of Pann Craft in the development of ceramic products it produces. The development of ceramic products that has been done produce various products with a variety of themes, form, function and dimensions, and colors.Keywords: products, development, design, ceramics